Spleen tyrosine kinase expression is correlated with human papillomavirus in head and neck cancer. (February 2020) - Black, Morgan; Ghasemi, Farhad; Sun, Ren X.; Stecho, William; Datti, Alessandro; Meens, Jalna; Pinto, Nicole; Ruicci, Kara M.; Khan, M. Imran; Han, Myung Woul; Shaikh, Mushfiq; Yoo, John; et al.
Highlights: High SYK expression is observed in HPV-positive HNSCC tumors. Inhibition of SYK can control HNSCC cell line proliferation and migration. SYK inhibition reduces tumor burden in PDX models. Abstract: Objectives: Spleen tyrosine kinase (SYK) is a promoter of cell survival in a variety of cell types, including normal and cancerous epithelial cells. We hypothesized that SYK would an important therapeutic target to inhibit for the treatment of HNSCC. Materials and methods: SYK protein abundance in patient tumours was evaluated. SYK protein and mRNA abundance was used to examine patient survival and human papillomavirus (HPV) status. Small-interfering RNAs and gene editing with CRISPR/Cas9 were used to evaluate SYK expression on proliferation in HNSCC cell lines. The potency of SYK inhibitor ER27319 maleate on cellular proliferation was tested using a panel of 28 HNSCC cell lines and in vivo in HNSCC patient-derived xenograft (PDX) models. Results: Moderate to high protein expression of SYK was observed in 24% of patient tumors and high SYK expression was exclusively observed in HPV-positive samples ( p  < 0.001). SYK inhibition with RNA interference, gene editing or a SYK inhibitor (ER27319) decreased cell proliferation and migration. Treatment of PDXs with ER27319 maleate was observed to reduce tumour burden in vivo in two of three models. Conclusions: HPV-positive HNSCC harbours high SYK protein levels. We demonstrate that proliferation, migration and overall burden of these tumours can be reduced by genetic or pharmacologic inhibition of SYK. Taken together, these data establish SYK as a therapeutic target for HNSCC.